PENGEMBANGAN MEDIA PEMBELAJARAN MAKE A MATCH CARD BERBASIS QR CODE PADA PEMBELAJARAN IPAS KELAS IV SD TOPIK BAGIAN TUBUH TUMBUHAN - Virnanda Dualis Tanto; Nanang Khoirul Umam; Arya Setya Nugroho (Yayasan Nusantara Hasana Berdikari, 2024)
In the era of Industrial Revolution 4.0, the education system is expected to be able to realize that students have skills that are able to think critically and solve problems, be creative and innovative as well as communication and collaboration skills. Also skills in searching, managing and conveying information as well as skills in using information and technology. One media that can attract students is the QR code-based make a match card game. So the researcher wishes to conduct a research entitled